Copper - Reeves, P. G. (Sports Nutrition, Vitamins and Trace Elements, 1997)
The nutrient copper and its relationship to sports activities and exercise are reviewed. Copper is a required nutrient for humans. Without an adequate dietary source, health and physiological function can not be maintained. There is a need for copper in enzyme systems that regulate oxygen consumption, cardiovascular function and neurological function. The safe and adequate daily dietary intake of copper for the general adult population is 1.5 to 3.0 mg. There are indications that athletes may have a tendency to alter blood copper concentrations and increase losses in sweat and urine during exercise. Dietary surveys of athletes also indicate that, like the general populations, some may take in less than the recommended amount of copper. However, there has been no convincing evidence that low copper status exists in athletes who consume a well balanced diet of a variety of foods. It is highly recommended, therefore, that athletes obtain the required amount of copper by eating a variety of foods, including those with moderate to high amounts of copper such as oysters, liver, dried beans, potatoes, and nuts. Athletes should not rely upon dietary supplementation for copper or any other nutrient unless they are found to be lacking in the nutrient by clinically recognized tests conducted under the supervision of a qualified nutritionist of physician.